2005
DOI: 10.1007/s00221-005-2255-4
|View full text |Cite
|
Sign up to set email alerts
|

Hand movement observation by individuals born without hands: phantom limb experience constrains visual limb perception

Abstract: Increasing evidence suggests that the visual analysis of other people's actions depends upon the observer's own body representation or schema. This raises the question of how differences in observers' body structure and schema impact their perception of human movement. We investigated the visual experiences of two persons born without arms, one with and the other without phantom sensations. These participants, plus six normally-limbed control observers, viewed depictions of upper limb movement under conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 35 publications
6
45
0
Order By: Relevance
“…1B). This is consistent with data from healthy participants-one normally perceives the hand moving between the two positions through the long, physiological movement if the rate at which the two images alternate is equal to or slower than the speed at which they can perform the movement themselves (13). After training, the four successful participants perceived the impossible movement regardless of the rate at which images alternated but only for images of the amputated side.…”
Section: Resultssupporting
confidence: 85%
“…1B). This is consistent with data from healthy participants-one normally perceives the hand moving between the two positions through the long, physiological movement if the rate at which the two images alternate is equal to or slower than the speed at which they can perform the movement themselves (13). After training, the four successful participants perceived the impossible movement regardless of the rate at which images alternated but only for images of the amputated side.…”
Section: Resultssupporting
confidence: 85%
“…The Body and Proprioceptive Imagery 16 slower to mentally rotate their hands or feet into awkward postures than into postures that are biomechanically easier to achieve (Parsons, 1987(Parsons, , 1994Shenton et al, 2004;Funk et al, 2005). For example, judging the laterality of a picture of the palm of a hand orientated 90 o away from the medial axis (with the thumb pointing away from the body) is more difficult than for the same picture orientated towards the medial axis (Parsons, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested that participants perform this task by mentally rotating their hand from its current posture to match the seen hand (Parsons, 1987). Indeed, when the posture of the participant's own hand does not match that of the picture, responses are slowed (Shenton, Schwoebel, & Coslett, 2004;Funk, Shiffrar, & Brugger, 2005;Ionta, Fourkas, Fiorio, & Aglioti, 2007). The…”
Section: Introductionmentioning
confidence: 99%
“…1). In a paradigm investigating "apparent motion of body parts" (Shiffrar and Freid 1990), we compared AZ's performance with that of CL, a 43-year-old journalist born without arms, but who had never experienced any phantom sensations (Funk et al 2005). In this paradigm, what is seen is determined by what can be performed with one's limbs.…”
Section: Phantoms Of Congenitally Absent Limbs As Manifestations Of Tmentioning
confidence: 99%